Improved modelling of the fuel cell power module within a system-level model for solid-oxide fuel cell cogeneration systems - Carl, Michael; Djilali, Ned; Beausoleil-Morrison, Ian (Journal of power sources, 2010)
A generic system-level model for SOFC cogeneration devices has been developed under the umbrella of an International Energy Agency/Energy Conservation in Buildings and Community Systems project known as Annex 42. This paper addresses a limitation of the Annex 42 model by developing a more refined semi-mechanistic treatment for the fuel cell power module (FCPM). The electrochemical, thermal, and reformation modelling methods as well as techniques for treating the FCPM's balance of plant are first described. The methods used to calibrate and validate the enhanced model using previously collected data from a 2.8 kW AC prototype SOFC cogeneration device are then discussed. Excellent agreement was found between model predictions and the measurements. The new modelling capabilities are then demonstrated through a parametric study that examines the influences of fuel utilization, excess air ratio and stack temperature.